A afetividade e as expressões de agressividade na educação infantil - FERREIRA, Fernanda Rosiely Alves (2023)
The actual study consists of analyzing and understanding the meanings produced about affectivity in early childhood education, concerning aggressiveness expressions and what is the school, family and society role in this context. The literature mentioned tells us that there shouldn’t be a cognitive and affective aspects separation, because early childhood education must be organized in such a way that children develop their cognitive, affective, physical, ethical and aesthetic capacities. Here, I review the importance constitution social and interpersonal relationships and the environment influence during this process, with the school, family and society being responsible agents in the child’s education. Supported by exploratory- descriptive and qualitative research, five interviews were conducted with the faculty of two different schools. The interviews were conducted with the aim of: understanding the meanings produced by early childhood education professionals about affectivity and aggressive expressions, as well as understand the meanings about the family and the school role as agents involved in the constitution process and understanding about the different ways for children to express their emotions, in addition to understand the importance of working on this theme in the educational environment. Therewith, produce material that contributes to achieving the research objective. As soon, through this research, it is observed that affectivity is essential in educational performance, however, the participants speeches in line with the bibliographic survey, consider that the aggressiveness expressions in early childhood education are present in the current situation and it’s a social “problem”, therefore, it’s necessary to carry out projects and action measures involving the school work in partnership with all the agents involved, given that social interaction is directly related to the values construction that guide children's actions.